Terapia por fotobiomodulação com laser de baixa intensidade e sua associação com diclofenaco de sódio promove a resolução do processo inflamatório em modelo experimental de tendinite induzida por colagenase - Evaristo, Mateus Moura (2019)
Achilles tendinitis is frequent and difficult to treat, but there are a variety of therapies and treatments to address tendon injury. The most used today are anti-inflammatory drugs that present momentary but unsatisfactory results due to their undesirable effects and damage to tissue repair. Photobiomodulation therapy appears as a promising therapy in modulating acute and chronic inflammatory process with no adverse effects caused by anti- inflammatory drugs. The present study aimed to evaluate the action of diclofenac sodium associated with photobiomodulation therapy in the resolution of tendinitis inflammation. Male Wistar rats were anesthetized and induced by collagenase injection tendinitis (100µg/paw) on the calcaneal tendon. The animals were divided into 4 groups: Control (CTL) with untreated induced tendinitis, Sodium Diclofenac treated Induced Tendinitis (DIC) or Low Intensity Laser treated (PBM). A group with associated therapies (Laser and Diclofenac sodium - PBM + DIC) was also included. Two hours after tendinitis induction and treatment, the animals were euthanized and the tendons isolated for histological, molecular (gene expression of ALX, ERV, BLT1 and DRV1) and biochemical (Myeloperoxidase Activity - MPO) analysis. Results: The PBM group showed an increase in ALX and ERV expression, and a decrease in BLT1, compared to the CTL group. The DIC group showed a decrease in ALX and ERV expression and an increase in BLT1 when compared to the irradiated groups. All treated groups showed a reduction in inflammatory infiltrate compared to the CTL group. The PBM + DIC group showed an increase in ALX and ERV expression, and a decrease in BLT1 when compared to the control and DIC groups. Our work suggests that low level laser therapy (810nm - 3J and 30mW) associated or not with sodium diclofenac helped to reduce the inflammatory infiltrate and increase the expression of important receptors related to the inflammation resolution process.